Accreditation framework for military independent clinical centers in Iran - Serajaddin Gray; Saeed Bayyenat (Tehran University of Medical Sciences, 2020)
Background: In Iran, the accreditation system is mainly focused on hospitals and has not yet succeeded in providing standards for independent medical centers such as independent clinics. The present study reports the development of an accreditation framework for independent clinics affiliated with the country's armed forces. Materials & Methods: This is a mixed (qualitative-quantitative) study. Experts' agreement (30 people) on the results of a systematic review (201 items) was obtained using a questionnaire and through holding three expert panels. The necessity of each item was calculated using the method of content validity ratio and the weight of standards and headings based on the average. Results: The existing 201 items were converted into 75 standards in 13 headings as final standards with the weight of each item. Conclusion: This framework can be used as a comparison tool between independent medical centers and it is necessary to train evaluators, and prepare legal and organizational requirements in order to implement it.